Equation of state with an extended SU(3) quark-meson model under conditions prevailing in core collapse supernovae - Beisitzer, Thomas; Stiele, Rainer; Schaffner-Bielich, Jürgen (Physical review. D, Particles, fields, gravitation, and cosmology, 2014)
The quark-meson model is investigated for the two- and three-flavor case extended by contributions of vector mesons under conditions encountered in core-collapse supernova matter. Typical temperature ranges, densities, and electron fractions, as found in core-collapse supernova simulations, are studied by implementing charge neutrality and local β equilibrium with respect to weak interactions. Within this framework, we analyze the resulting phase diagram and equation of state (EoS) and investigate the impact of undetermined parameters of the model. The EoS turns out to be relatively independent on the entropy per baryon but there are significant changes when going from the two-flavor to the three-flavor case due to the nontrivial contribution from the strange quarks which stay massive even at high densities. While an increasing vector meson coupling constant leads to a substantial stiffening of the EoS, we find that the impact of changing the scalar meson mass is equally strong and results in a softening of the EoS for increasing values.